Fluorine toxicity in citrus: Growth retardation and leaf tip-burn accompanied increased fIuorine concentrations in experimentaI laboratory cultures - A Haas; J Brusca (California Agriculture, 1955)
Foliage injury in certain fruit tree varieties has been reported as being quite serious when the leaves were subject to hydrogen fluoride or fluorine deposits. Leaf tip-burn resulted in gladiolus plants when exposure was made to various concentrations of fluorine gas. Leaves of citrus trees located in close proximity to gaseous sources of fluorine are reported as containing an increased content of fluorine. Fluorides are known to occur in certain crude phosphate materials, the very sources from which fertilizers are prepared.